Optimizing BAP and NAA Concentrations for In Vitro Shoot Initiation of Black Potato (Plectranthus rotundifolius) - Eristiana, Aprilia; Nikmatullah, Aluh; Kisman, Kisman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Black potato (Plectranthus rotundifolius (Poir.) Spreng.) has potential as an alternative food crop, but the limited availability of high-quality planting material necessitates in vitro propagation. This study evaluated the effect of Benzylaminopurine (BAP) and Naphthaleneacetic Acid (NAA) combinations on the initiation-stage growth of black potato shoot explants. A factorial Completely Randomized Design (CRD) with 16 treatment combinations, three replications, and 48 experimental units was used. Quantitative data were analyzed using Analysis of Variance (ANOVA) followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level, while qualitative data were analyzed descriptively. The combination of BAP and NAA significantly affected root emergence time (p = 0.019), number of roots (p = 0.002), number of leaves (p = 0.013), and fresh weight of plantlets (p = 0.001), but had no significant effect on shoot emergence, callus emergence, shoot number, shoot length, root length, or dry weight (p > 0.05). Treatment B0N3 produced the highest number of roots (11.33 roots explant⁻¹), B1N0 produced the highest number of leaves (8.33 leaves explant⁻¹), and B3N3 resulted in the highest fresh weight (1.48 g). These findings indicate that NAA alone was more effective for root induction, whereas higher BAP–NAA combinations promoted greater plantlet biomass accumulation.